Analisis Proses Adaptasi Sosial dan Pengendalian Depresi dalam Upaya Peningkatan Kualitas Hidup Lansia Terlantar di Sasana Tresna Werdha Dukuh 5, Kramat Jati Tahun 2023-2024 - Marselia Wulansari Utami; Tri Budi W. Rahardjo; Tri Suratmi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The global elderly population in 2022 was 1.4 billion, and in ASEAN, the number of elderly people reached 142 million or 8% of the population. Indonesia has become an aging population since 2021 with 10% of its population being elderly, reaching 28.9 million people in 2022, with 1 elderly person supported by 6 productive residents (BPS, 2022). In DKI Jakarta, there are 951,557 elderly people with 2,340 elderly people in Kelurahan Dukuh (Jakarta Open Data, 2020). The increasing number of elderly people indicates successful development, but unproductive, financially weak, sick elderly people without social security and needing assistance can become an economic burden (BKKBN, 2020). Neglected elderly are at risk of becoming PMKS and are fostered by the Social Service. These elderly people need social adaptation and are vulnerable to depression. This study aims to analyze the process of social adaptation and depression control in an effort to improve the quality of life of neglected elderly at Sasana Tresna Werdha Dukuh 5, 2023-2024. The observational study uses a sequential explanatory mixed-method approach with surveys and in-depth interviews as well as FGDs, using 19 respondents. The results show that 89.47% of respondents are young elderly, 68.42% show moderate social adaptation, 10.53% mild depression, and 26.32% have a moderate quality of life. Some of these elderly people experience social adaptation disorders and schizophrenia, as well as severe social problems. ASN and PJLP lack knowledge about mental disorders, especially depression. In conclusion, most neglected elderly fostered by PSTW experience good self-adaptation, do not experience depression, and have a good quality of life, but some elderly people are found to experience severe depression and moderate quality of life. Special education on mental health for ASN and PJLP is very necessary.